Challenges of implementation of hospital accreditation in Iran: an exploratory factor analysis - Narges Tashayoei; Pouran Raeissi; Amir Ashkan Nasiripour (SpringerOpen, 2020)
Abstract Background Today, accreditation is considered as the most commonly used health assessment approach. Considering the importance and application of the process of this approach in the hospital, this study aimed to investigate the challenges of implementation of hospital accreditation in Iran using exploratory factor analysis. Methods A cross-sectional study design was carried out from July to December 2017, consisting of 200 managers in the seven hospitals accredited by the MOH in Tehran, Iran. Samples were selected through the purposive sampling method, and data were collected using a structured questionnaire in which validity and reliability were confirmed. Likert's five-choice range was used for the rating of items. Exploratory factor analysis was used to categorize the identified challenges and extract the mathematical model on them. Results Exploratory factor analysis identified six dimensions (implementation, evaluation, content, structural, psychological, and managerial) with 40 items using a 5-point Likert scale. Each dimension accounted for greater than 63.20% of the total variance. The scale had strong content validity (indices = 0.84). Each dimension of Cronbach's alpha ranged from 0.74 to 0.94. Implementation, evaluation, content, structural, psychological, and managerial components also formed the final identified areas. Conclusion The present study showed that there were major challenges in the path to successful deployment of Iranian hospital accreditation, requiring serious action by managers and policymakers in this field.